2023
DOI: 10.3389/fmicb.2023.1178474
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of plastic-degrading microbial strains isolated from the alpine and Arctic terrestrial plastisphere

Abstract: Increasing plastic production and the release of some plastic in to the environment highlight the need for circular plastic economy. Microorganisms have a great potential to enable a more sustainable plastic economy by biodegradation and enzymatic recycling of polymers. Temperature is a crucial parameter affecting biodegradation rates, but so far microbial plastic degradation has mostly been studied at temperatures above 20°C. Here, we isolated 34 cold-adapted microbial strains from the plastisphere using plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Nevertheless, based on the phenotypic screening results, they proved to be interesting candidates for PU degradation. Streptomyces strains have been previously reported to degrade Impranil in plate assays (Rüthi et al., 2023 ), but no in‐depth study on Streptomyces PU degradation was performed. Recent studies have reported fungal strains capable of reaching high levels of the same Impranil degradation, such as Embarria clematidis that could degrade 88.8% of 1% (v/v) Impranil after 2 weeks of incubation (Khruengsai et al., 2022 ) while Cladosporium strains could degrade 80% and 94.4% in 3 days (Liu, Ahmad, et al., 2023 ; Zhang et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, based on the phenotypic screening results, they proved to be interesting candidates for PU degradation. Streptomyces strains have been previously reported to degrade Impranil in plate assays (Rüthi et al., 2023 ), but no in‐depth study on Streptomyces PU degradation was performed. Recent studies have reported fungal strains capable of reaching high levels of the same Impranil degradation, such as Embarria clematidis that could degrade 88.8% of 1% (v/v) Impranil after 2 weeks of incubation (Khruengsai et al., 2022 ) while Cladosporium strains could degrade 80% and 94.4% in 3 days (Liu, Ahmad, et al., 2023 ; Zhang et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In doing so, we have identified several areas where the use of this approach in the future could advance marine plastisphere research: Firstly, in the assessment of temperature and sunlight (in addition to other environmental factors) as key factors regulating protein expression and community metabolism to define the trophic status of the plastisphere as a feature of location. Although still an emerging research topic, this appears to play a pivotal role in the presence of hydrocarbonoclastic lineages [ 20 , 85 , 86 ], driving the potential for biodegradation within the plastisphere, with the success of bioremediation potentially improved through increased focus on cold-adapted metabolisms [ 54 , 87 ]. Secondly, by improving the overall functional representation of the marine plastisphere, the sensitivity of techniques such as comparative metaproteomics can be continually improved through the development of specific databases which capture the diversity of peptide and protein sequences truly present in this environment [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ice and snow samples were processed the same way, except for an initial melting step at 4°C before plating. R2A agar was chosen due to the suitability of cryospheric organisms to grow best on oligotrophic media ( Rüthi et al, 2023 ). Morphological different colonies from all samples were described, transferred into 7 mL of lysogeny broth (LB-media) with a sterile loop, and incubated for 7 days at the respective temperature.…”
Section: Methodsmentioning
confidence: 99%